Review of Gray’s beaked whale (Mesoplodon grayi) in the South East Pacific - Canto Hernández, Jhoann; D'Elía, Guillermo; Cadenillas, Richard; Toro, Frederick; Borroni, Cintya; Cerda, Gerardo; Español-Jiménez, Sonia (THERYA, 2022)
Information collected from a complete female juvenile individual of Gray's beaked whale (Mesoplodon grayi) stranded on the Guanaqueros coast, Coquimbo Region in Chile (30Â°S) is provided. Difficulties to differentiate specimens of Gray's beaked whale and Hectorâ€™s beaked whale (M. hectori) are discussed based on the use of diagnostic phenotypic characters, such as differences in color patterns and position of teeth on the lower jaw. The identification of the studied specimen as Gray's beaked whale was supported by a detailed review of cranial characters and molecular analyses. Finally, we provide an updated list containing all known Chilean records for this species.